A scalable and secure position-based routing protocols for ad-hoc networks - Qabajeh, L.K.; Kiah, M.L.M.; Qabajeh, M.M. (2009)
Mobile Ad-Hoc Networks (MANETs) are becoming increasingly popular as more and more mobile devices find their way to the public. A crucial problem in Ad-Hoc networks is finding an efficient route between a source and a destination. Due to MANETâs inherent characteristics, secure routing may be one of the most difficult areas to tackle because opponents can add themselves to a MANET using the existing common routing protocols. Hence, this paper proposed a new model of routing protocol called ARANz, which is an extension of the original Authenticated Routing for Ad-Hoc Networks (ARAN). Apart from the authentication methods adopted from ARAN, ARANz aims to increase security, achieve robustness and solve the single point of failure and attack problems by introducing multiple Local Certificate Authority servers. Moreover, by dealing with the network as zones and using restricted directional flooding, our new model will exhibit better scalability and performance. An overview and a qualitative comparison between ARANz and some existing Ad-Hoc routing protocols is presented in this paper.